Alloy Crystal Structure and Volumetric Mass Density Analysis - Dirasutisna, D Tamara; Adjiantoro, Bintang; Sihombing, Sarinah; Rifni, Muhammad; Gugat, Ruddy Max Damara (Journal of Social Research, 2023)
Volumetric mass density and changes in crystal structure analysis of Sn-xBi alloy and Sn-xBi-yAl alloys have been conducted to enhance our understanding of these materials. The Sn-xBi alloy, with various compositions including Sn-0Bi, Sn-10Bi, Sn-30Bi, Sn-52Bi, and Sn-70Bi, and the Sn-xBi-yAl alloys, with compositions including Sn-52Bi-0.05Al, Sn-52Bi-0.11Al, Sn-52Bi-0.14Al, Sn-52Bi-0.19Al, and Sn-52Bi-0.25Al, were synthesized for this research. The selection of Sn-xBi-yAl compositions was based on the optimal composition of Sn-xBi alloys, specifically Sn-52Bi, which possesses the lowest melting point at 142.8°C. The determination of melting points was carried out using the Differential Scanning Calorimetry (DSC) method. Crystal structure characterization was accomplished using X-ray diffraction (XRD) techniques, with subsequent analysis performed through the Generalized Structure Analysis System (GSAS) method. These investigations are pivotal as they provide insights into the material properties and structural changes in Sn-xBi and Sn-xBi-yAl alloys, which have significant implications in various industrial applications and technological advancements. The results of this research are expected to contribute to the optimization of these alloy systems, leading to improved performance and potential innovations in materials science and engineering.